THE HISTORY OF THE FORMATION AND DEVELOPMENT OF THE GEO-ECONOMIC THINKING OF THE OWNERS ON THE EXAMPLE OF THE GREAT SILK ROAD (Analysis of International Sciences, 2024)
In the article the author considers the example of the Great silk road the history and originality of the formation and development of geo-economic thinking of the owners from a historical point of view.